Is the Left Kidney the Right One for Kidney Donation in Women Planning on Future Pregnancy? - H K?ran; G K?ran; D Ar?kan; M Yzba??o?lu; M Bakacak; Ercan; B Kst (International Journal of Organ Transplantation Medicine, 2015)
The kidney transplantation surgery requires left nephrectomy because of the anatomical disadvantages. But hydroureteronephrosis is the most significant renal functional alteration of pregnancy, accounted for by both hormonal and mechanical factors. Dilatation of the ureters and renal pelvis is more prominent on the right side than the left side and is seen in up to 80% of pregnant women. A 23-year-old woman who become pregnant after 4 months from left kidney donation was admitted to our emergency department with acute right kidney injury during her 39th week of pregnancy. She did not response to conservative treatment and required emergency delivery because of the progressive increase in her serum creatinine levels. After delivery, progressive decrease at creatinine level had been observed and in one month, it had reached the normal level. Mother candidates should be advised they donate their kidneys after completing their childbearing if possible, or undergo right nephrectomy.